SWOT Analysis and Customer Satisfaction: Laundry Business Optimization Strategy - Putra, Carolus Andro Novalgi; Kusumawardhana, Firdaus Eka; Akmal, Muhammad Wahid; Susanto, Yosep Ferry (Innovation, Technology, and Entrepreneurship Journal, 2024)
This research aims to analyse the company's vision, mission, and internal and external conditions while establishing a strategy for the Laundry business to improve the business and meet customer needs. The state of its business greatly influences an organization's business strategy. Organizations can better understand the company's internal and external conditions through SWOT analysis. It also allows companies to create strategies that suit industry competition. After analysing the SWOT, further analysis was carried out using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) methods. It is a foundation for organizations to exploit weaknesses and opportunities to reduce weaknesses and deal with threats. This research uses descriptive qualitative as an analysis method. The primary data for this research comes from interviews with laundry business owners in Kocoran, Caturtunggal, Kec. Depok, Sleman Regency, Special Region of Yogyakarta 55281. In general, the results of this research show that the strategy implemented can increase competitiveness and meet customer needs more effectively.